Reinforcement Corrosion Characteristics with Periodical Profile - Bondar, Viktor; Bondar, Liudmyla; Petrash, Oleksandr (International Journal of Engineering and Technology, 2018)
The theoretical analysis of corrosion processes on the periodical profile reinforcement in low potential corrosion environment has been conducted using a mathematical model. The boundary between liquid and metal phases in the model was set by a sinusoidal laxly concaved profile. In this research, itâ€™s been suggested the hypothesis that mass transfer of cathodic and anodic depolarizers on the surface of corroborated reinforcement is defined by diffusion such that current density is constant on long distance from the boundary between the phases. The Laplacian equation has been solved by perturbation method representing concentrations as mathematical row by a small parameter. It has been analyzed the possibility of occurring a liquid coating under the concrete protective layer on the reinforcement surface in the contact spots between the ribs and reinforcement body. Itâ€™s been discovered how the profile geometry impacts the distribution of corrosion current. Â